2022
DOI: 10.1007/s40264-022-01186-z
|View full text |Cite
|
Sign up to set email alerts
|

Signaling COVID-19 Vaccine Adverse Events

Abstract: Introduction Statistical signal detection is a crucial tool for rapidly identifying potential risks associated with pharmaceutical products. The unprecedented environment created by the coronavirus disease 2019 (COVID-19) pandemic for vaccine surveillance predisposes commonly applied signal detection methodologies to a statistical issue called the masking effect, in which signals for a vaccine of interest are hidden by the presence of other reported vaccines. This masking effect may in turn limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Disproportionality analysis was not feasible for the Dutch spontaneous reporting system due to the large volume of reported AEFIs for the COVID-19 vaccines and selective reporting for certain AEFI. 40,41,52 In conclusion, this Dutch CEM study found an incidence of menstrual disorders of 41.4 per 1000 female participants aged ≤54 years.…”
Section: Use Of Contraceptivesmentioning
confidence: 64%
“…Disproportionality analysis was not feasible for the Dutch spontaneous reporting system due to the large volume of reported AEFIs for the COVID-19 vaccines and selective reporting for certain AEFI. 40,41,52 In conclusion, this Dutch CEM study found an incidence of menstrual disorders of 41.4 per 1000 female participants aged ≤54 years.…”
Section: Use Of Contraceptivesmentioning
confidence: 64%
“…Interestingly, in the US Vaccine Adverse Event Reporting System (VAERS), masking has been found to be rare overall, but more likely to affect COVID-19 vaccines than other vaccines, and regressionbased methodologies may help address the problem. 56 On generating near real-time, real-world evidence…”
Section: Lessons Learned On Facing a Massive Influx Of Spontaneous Re...mentioning
confidence: 99%
“…The large contribution of certain COVID‐19 vaccines to reports in EudraVigilance has an impact on reporting odds ratios for other COVID‐19 vaccines and other medicines, with signals being masked or false associations being flagged as potential signals. Interestingly, in the US Vaccine Adverse Event Reporting System (VAERS), masking has been found to be rare overall, but more likely to affect COVID‐19 vaccines than other vaccines, and regression‐based methodologies may help address the problem 56 …”
Section: Lessons Learnedmentioning
confidence: 99%
“…With the rapid increase of submitted ICSRs however, the signal detection process adopted other quantitative approaches as well in order to handle the large datasets. Disproportionality analysis, using reporting odds ratios, was deemed less useful during the large‐scaled COVID‐19 vaccination campaign due to issues like statistical masking effect 21 …”
Section: Introductionmentioning
confidence: 99%
“…Disproportionality analysis, using reporting odds ratios, was deemed less useful during the large-scaled COVID-19 vaccination campaign due to issues like statistical masking effect. 21 In addition, since vaccination campaigns included a large part of the population, the numbers of a reported specific adverse reaction should be placed in perspective with background incidence rates of these clinical events became in assessing whether an association with the suspect drug is plausible. In May 2020, the ACCESS (The vACCine Covid-19 monitoring readinESS) project was launched to prepare real-world monitoring of COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%